2012
DOI: 10.1039/c2ce25980j
|View full text |Cite
|
Sign up to set email alerts
|

Precursor-dependent shape variation of wurtzite CdSe crystals in a microwave-assisted polyol process

Abstract: We report a unique synthetic approach to fabricate CdSe crystals with tunable morphology and optical properties via a microwave-assisted polyol process. The morphology of CdSe crystals has been controlled by adjusting the relative amounts of two cadmium precursors CdCl 2 and CdO in a polyol solvent of ethylene glycol or glycerol; spheres, pebbles, sheets, and tetrapods of CdSe wurtzite structures with their sizes ranged from nanometers to sub-micrometers have been prepared facilely under microwave irradiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…The development of various morphologies for Mn 2 O 3 has been investigated by different synthetic methodologies as a function of salt concentration, pH of the medium, solvent types, templates, and reaction temperature. There are examples of precursor dependent morphology evolution in case of ZnO, CdS, Cu 2 S and CdSe . Similar studies for the manganese‐based oxides are not reported to the best of our knowledge.…”
Section: Introductionsupporting
confidence: 66%
“…The development of various morphologies for Mn 2 O 3 has been investigated by different synthetic methodologies as a function of salt concentration, pH of the medium, solvent types, templates, and reaction temperature. There are examples of precursor dependent morphology evolution in case of ZnO, CdS, Cu 2 S and CdSe . Similar studies for the manganese‐based oxides are not reported to the best of our knowledge.…”
Section: Introductionsupporting
confidence: 66%
“…The authors interpret the anisotropic growth of the (CdSe) n nanocrystals using the 1950 model in a qualitative discussion and using two different curves (Fig. 8c of that paper 131 ), one with a short time-span in the nucleation stage for the low solubility CdO precursor and one with a long time-span in the nucleation stage for CdCl 2 , which is highly…”
Section: Formation Of Semiconductor Nanoparticles By the ''Heating-up'' Methodsmentioning
confidence: 99%
“…The controlled fabrication, characterization, and application of nanoscale materials have been studied widely due to their functional properties. [1][2][3][4] Colloidal semiconductor nanocrystals, also called ''quantum dots'' (QDs), are middle-stage materials, which are between atoms or molecules having discontinuous electronic-energy levels and bulk materials having continuous electronic-energy bands. Thus, the study of nanocrystals has been one of the most important subjects about the fundamental understanding of nanosized materials as well as the successful application of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%